A new species of Ansonia (Anura: Bufonidae) from northern Tanintharyi Division, Myanmar - Wilkinson, Jeffery A.; Sellas, Anna B.; Vindum, Jens V. (Zootaxa, 2012)
A new species of Ansonia is described from northern Tanintharyi Division, Myanmar. The new species is the first recordof Ansonia from Myanmar. It is phylogenetically most closely related to A. kraensis at the Isthmus of Kra, Thailand, butcan be distinguished from A. kraensis and all other species of Ansonia from Thailand and the Malay Peninsula by a combination of several morphological characters and dorsal and ventral color patterns.